2006
DOI: 10.1093/pcp/pcl005
|View full text |Cite
|
Sign up to set email alerts
|

Ferredoxin Limits Cyclic Electron Flow around PSI (CEF-PSI) in Higher Plants—Stimulation of CEF-PSI enhances Non-Photochemical Quenching of Chl Fluorescence in Transplastomic Tobacco

Abstract: We tested the hypothesis that ferredoxin (Fd) limits the activity of cyclic electron flow around PSI (CEF-PSI) in vivo and that the relief of this limitation promotes the non-photochemical quenching (NPQ) of Chl fluorescence. In transplastomic tobacco (Nicotiana tabacum cv Xanthi) expressing Fd from Arabidopsis (Arabidopsis thaliana) in its chloroplasts, the minimum yield (F(o)) of Chl fluorescence was higher than in the wild type. F(o) was suppressed to the wild-type level upon illumination with far-red light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 65 publications
3
42
1
Order By: Relevance
“…The characteristics displayed by OeFd1 plants contrast with those reported by Yamamoto et al (2006), who observed no significant phenotypic alterations in transplastomic tobacco plants expressing the major Fd isoprotein of Arabidopsis, AtFd2, which is known to be predominantly involved in LEF. Indeed, many of the features observed in OeFd1 lines actually resembled those normally exhibited by Fd-deficient (antisense or silenced) plants (Holtgrefe et al, 2003;Blanco et al, 2011), although the levels of endogenous tobacco Fd were not affected in OeFd1 lines (Fig.…”
Section: Chlorophyll Fluorescence Parameters In Oefd1 Plantscontrasting
confidence: 89%
See 1 more Smart Citation
“…The characteristics displayed by OeFd1 plants contrast with those reported by Yamamoto et al (2006), who observed no significant phenotypic alterations in transplastomic tobacco plants expressing the major Fd isoprotein of Arabidopsis, AtFd2, which is known to be predominantly involved in LEF. Indeed, many of the features observed in OeFd1 lines actually resembled those normally exhibited by Fd-deficient (antisense or silenced) plants (Holtgrefe et al, 2003;Blanco et al, 2011), although the levels of endogenous tobacco Fd were not affected in OeFd1 lines (Fig.…”
Section: Chlorophyll Fluorescence Parameters In Oefd1 Plantscontrasting
confidence: 89%
“…Until now, the only work concerning this issue has been the expression of the major Arabidopsis isoprotein, AtFd2, in tobacco (Nicotiana tabacum) chloroplasts using a transplastomic strategy. The transgenic plants obtained did not show a dramatic phenotype, and the CEF-PSI was enhanced only at high-light growth intensities (Yamamoto et al, 2006). However, no attempt has yet been made to overexpress one of the minor Fd isoproteins, which have been proposed to differentially operate in CEF.…”
mentioning
confidence: 96%
“…The milder phenotype is probably related to the fact that Fd is engaged in electron distribution to other chloroplast processes besides NADP 1 reduction and therefore accumulates above the levels of other PETC components, reaching a concentration of about 80 mM (YonekuraSakakibara et al, 2000). In line with the observations reported here for plants accumulating higher content of FNR, overexpression of shuttle members of the PETC, such as Fd (Yamamoto et al, 2006) or plastocyanin (Last and Gray, 1990) in chloroplasts failed to improve growth or photosynthesis in transgenic tobacco lines. The existence of several kinetic constraints in photosynthetic electron transport explains why FNR only becomes limiting when it is underexpressed in antisense plants.…”
Section: Photosynthesis In Fnr-supporting
confidence: 88%
“…In addition, more dynamic models that illustrate competitive processes involved in the distribution of electrons between the cyclic and linear flows have been proposed. The competition between cytochrome b 6 /f and FNR for electrons from Fd could regulate the segregation between LEF and CEF (Breyton et al, 2006;Yamamoto et al, 2006;Hald et al, 2008). A few years ago, Joliot and Joliot (2006) suggested that the ATP/ ADP ratio was one of the parameters that triggered on the transition between LEF and CEF.…”
mentioning
confidence: 99%